Women’s Language Used in ‘Birds of Prey and the Fantabulous Emancipation of One Harley Quinn’ movie - Zulfadli Abdul Aziz; Masrizal Mahmud; Dista Nurhasanah (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
The purpose of this study is to analyze the major features of womenâ€™s language used by the female characters in â€œBirds of Prey and the Fantabulous Emancipation of One Harley Quinnâ€ movie. This study investigates the types of women speech features found in the movie. A qualitative approach employing a content analysis method was used in this study. The data were taken from female charactersâ€™ utterances. The data were then identified and analyzed based on the classifications of womenâ€™s speech features proposed by Lakoff (1975). Findings of this study indicate that six of the features are used by the female characters: lexical hedges/fillers, empty adjectives, tag questions, super polite forms, avoiding strong words, and emphatic stress. Rising intonation, precise color terms, intensifiers, and hypercorrect grammar have not been found in the current research data.